Implementation of Self-Help Housing Stimulant Assistance (BSPS) Program to Enhance the Tulang Bawang Community Prosperity - Siska Dwi Azizah Warganegara (Fakultas Hukum Universitas Lampung, 2020)
Every citizen has the right to live in prosperity both physically and mentally, with the fulfillment of physical, spiritual and social needs. To meet these needs the government has made a policy in the form of the Self-Help Housing Stimulant Assistance Program (BSPS), which aims to stimulate low-income communities to build / repair respective homes. The problem in this article is the urgency of housing policy through the BSPS Program in improving the welfare of the community in Tulang Bawang Regency? How is the implementation of housing policy through the BSPS Program in Tulang Bawang Regency? The research used a normative juridical and an empirical approach method. The data are primary and secondary. The result of the research shows that the urgency of housing policy through the BSPS Program is to meet the needs of the community in the form a decent house for habitation which is in line with the state's goals for the welfare of the people. One of them is the fulfillment of a house that is suitable for habitation and health, including building safety, reliability of structural components, improving the quality of non-structural component materials, health of lighting occupants, ventilation and sanitation as well as the minimum adequacy of building area. The BSPS policy in Tulang Bawang Regency is based on the PUPR Ministerial Regulation Number 07 of 2018 concerning BSPS, Perbup Tulang Bawang Number 36 of 2018 concerning Guidelines for Implementing Home Improvement Activities Sourced from the Regional Revenue and Expenditure Budget of Tulang Bawang Regency. The implementation of BSPS until 2019 has only been 7% (800) of 11,473 uninhabitable housing units (RTLH). In its implementation, BSPS has not been able to encourage public awareness of working together in building houses, according to the spirit of giving BSPS and giving BSPS there are still some that have not been on target. Judging from the benefits of the government housing policy, it can continue the policy for all low-income people (MBR), and future implementation can be carried out more selectively and on target.